Answer:
X=-6
Step-by-step explanation:
Answer:
<em>x = -6</em>
Step-by-step explanation:
<u>Equations</u>
Solve the equation:
x + 6 = -x - 6
We must find the value of x that makes the identity above true.
Let's join all the variables on the left side and the numbers on the right side.
Adding x:
x + 6 + x = -x - 6 + x
The variables cancel out on the right side:
2x + 6 = -6
Subtracting 6:
2x + 6 - 6 = -6 -6
The 6 and -6 are canceled out:
2x = -12
Dividing by 2:
x = -12/2
x = -6
(2/5) / 1 = x / (3/4).....2/5 cups to 1 pie = x cups to 3/4 pie
cross multiply
(1)(x) = (2/5)(3/4)
x = 6/20 which reduces to 3/10 cups <==